Trehalose-6-phosphate synthase 1, which catalyses the first step in trehalose synthesis, is essential for Arabidopsis embryo maturation. - Eastmond, P; van Dijken, A; Spielman, M; Kerr, A; Tissier, A; Dickinson, H; Jones, J; Smeekens, S; Graham, I (2002)
Despite the recent discovery that trehalose synthesis is widespread in higher plants very little is known about its physiological significance. Here we report on an Arabidopsis mutant (tps1), disrupted in a gene encoding the first enzyme of trehalose biosynthesis (trehalose-6-phosphate synthase). The tps1 mutant is a recessive embryo lethal. Embryo morphogenesis is normal but development is retarded and stalls early in the phase of cell expansion and storage reserve accumulation. TPS1 is transiently up-regulated at this same developmental stage and is required for the full expression of seed maturation marker genes (2S2 and OLEOSN2). Sucrose levels also increase rapidly in seeds during the onset of cell expansion. In Saccharomyces cerevisiae trehalose-6-phosphate (T-6-P) is required to regulate sugar influx into glycolysis via the inhibition of hexokinase and a deficiency in TPS1 prevents growth on sugars (Thevelein and Hohmann, 1995). The growth of Arabidopsis tps1-1 embryos can be partially rescued in vitro by reducing the sucrose level. However, T-6-P is not an inhibitor of AtHXK1 or AtHXK2. Nor does reducing hexokinase activity rescue tps1-1 embryo growth. Our data establish for the first time that an enzyme of trehalose metabolism is essential in plants and is implicated in the regulation of sugar metabolism/embryo development via a different mechanism to that reported in S. cerevisiae.